Development of Interactive Teaching Materials based on PBL Learning Models to Improve Students' Mathematical Reasoning Ability - Fadwa Syahida; Glory Indira D. Purba (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
The purpose of this study was to determine the feasibility of interactive teaching materials from the aspects of validity, practicality, and effectiveness, as well as to determine the increase in the mathematical reasoning abilities of students who were given learning using interactive teaching materials. The development model used is the ADDIE Model (Analyze, Design, Development, Implementation, and evaluation). The research instruments used in this study were media validation sheets, material validation sheets, Learning Implementation Plan (RPP) validation sheets, test validation sheets, mathematical reasoning ability tests, teacher response questionnaires and student response questionnaires. The results of this study showed a validity of 4.75 for media and 4.81 for material with very valid categories. practicality shows a percentage of 91% based on teacher responses and 86% based on student responses, both of which are in the very practical category.